Virgin Coconut Oil for HIV - Positive People - Widhiarta , Kadek Dharma (International Coconut Community Journal, 2016)
The objective of the study was to determine effects of 3 x 15 ml/day Virgin Coconut Oil supplementation for 6 weeks in subject to CD4+ T lymphocyte concentration and conducted at Special health center on Dharmais Cancer Hospital, Jakarta. The methods involved experimental study with parallel design on 40 HIV subject with CD4+ T lymphocyte count > 200 cell/µL divided into two groups, VCO group, subject in this group received VCO supplementation 3 x 15 ml/day for 6 weeks and non-VCO Group (without VCO supplementation). Data collected includes demographic characteristic (age and sex), anthropometric (weight, height, and body mass index), daily intakes by food recall 1 x 24 hours and laboratory (CD4+ T lymphocyte count). Statistical analysis was performed with independent t test and Mann-Whitney U test. The results could be summarised as follows. The average BMI were 20.8 ± 2.29 kgs/sqm (VCO group) and 20.7 ± 3.38 kgs/sqm (non-VCO group). Energy and fat intake between VCO group (1459 ± 327.4 Cal/day and 81.8 ± 19.35 gs/day) and non-VCO group (1101 ± 319.8 Cal/day and 37.1 ± 19.35 gs/day). Carbohydrate and protein intake between VCO group (143.8 ± 44.58 gs/day and 41.6 ± 14.04 gs/day) and non-VCO group (151.6 ± 14.04 gs/day and 39.5 ± 18.31gs/day). There were significant differences (p = 0.047) in average of CD4+ T lymphocyte count after 6 weeks intervention between VCO group (481 ± 210.0 cell/µL) and non-VCO group (343 ± 129.1 cell/µL). The conclusion is that Virgin Coconut Oil supplementation 3 x 15 ml/day for 6 weeks increases CD4+ T lymphocyte concentration in HIV patient.